Valorization of Algerian Semi-Soft Date and Traditional Preparation of Date Syrup: Physicochemical and Biochemical Properties - Laouar, Asma; Benbelkhir, Amina; Baida, Wahiba; Rouissat, Linda; BENYAGOUB, Elhassan (Indonesian Food Science and Technology Journal, 2021)
In Algeria, the production of dates occupies a large part of Saharan agricultural production. The wilaya of Bechar is one of the most productive regions for dates, where more than half of their production is considered as a second quality dates which are sold by barter or used as animal feed. Families in these regions use this type of date to prepare by-products, namely; date syrup locally called "Robb". The preparation of this type of product is limited and confined to the individual scale. The aim of this study is to highlight the physicochemical and the biochemical quality of this home-prepared artisanal product by comparing it to two others marketed in the wilaya of BÃ©char and of Elbayadh (Algeria). The physicochemical and the biochemical results of the three analyzed samples showed an acidic pH value ranged from 4,26 to 4,7, a degree of acidity ranging from 8,2 to 12%, a soluble solids content of 64 to 75%, a total sugars and reducing sugar content of 51 to 63,6 and 40 to 52% respectively. While the water content is relatively high ranging from 28 to 37%, and a significant potassium ions content compared to sodium ions varies from 195 to 555 and from 5,8 to 137mg/L respectively. These characteristics are not only considered as a high added value to the product which enhances the value of the second-quality low marketing dates but also contributes to increasing their shelf life, constituting an economic priority for the oasisâ€™ inhabitants of the Southern Algeria region.